Planning Strategy and The Use of Information Technology in Higher Education: A Review Study in Kurdistan Region Government - Mazen Ismaeel Ghareb; Zanyar Ali Ahmed; Azad Abdullah Ameen (JOIV : International Journal on Informatics Visualization, 2019)
An apparently interminable scope of techniques and methodologies has developed to misuse the capability of innovation. The issue has not been a shortage of research. Actually a great many examinations identified with computer and learning has been distributed amid the recent decades. The issue has been one of comprehending the tremendous, and developing, group of accessible research. There is developing enthusiasm for utilizing the ability of new innovation in a productive and successful approach to meet the instructional and research needs of faculty and students. The utilization of data innovation is one of numerous means to accomplishing magnificence. However the recharged enthusiasm for promoting brilliance in advanced education through Information Technology has carried with it a more prominent accentuation on the requirement for high-bore administration in this limit. Capability, combination of learning, joint effort with industry, collaboration among grounds at different levels, helpful procurement endeavors, what's more, transferability of gaining starting with one organization then onto the next are immeasurably imperative components in the administration way to deal with IT in higher Education. In addition to an extensive literature review, this examination contemplate utilized a trial also, quantitative, self-planned and controlled overview instrument to decide the mentalities and qualified respondents, containing IT leaders, IT staff, also, executives in higher instructive at open and private colleges in Kurdistan Region Government.